2012
DOI: 10.1093/geront/gns108
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Among Kuwaitis Aged 50 Years or Older: Prevalence, Correlates, and Comorbidities

Abstract: Prevalence of overweight and obesity is alarmingly high among elderly Kuwaitis. The associated disease burden is substantial. Stakeholders should address the problem and launch national extensive health-promoting campaigns targeting perceptible lifestyle changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Second, students emerging from these health professional programmes need to support the overall health of their patients and their communities; one way is to serve as credible role models for health promotion (12,13). This is especially true in the current health climate where NCDs that are largely lifestyle related are the leading causes of premature death and disability in the Middle East including Kuwait (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Second, students emerging from these health professional programmes need to support the overall health of their patients and their communities; one way is to serve as credible role models for health promotion (12,13). This is especially true in the current health climate where NCDs that are largely lifestyle related are the leading causes of premature death and disability in the Middle East including Kuwait (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the objective of the study was to develop a whole wheat flour bread supplemented with chickpea flour that lowers glycemic response, decreases appetite and is acceptable to consumers. Kuwait being number one among the Arab countries in the prevalence of obesity, with an incidence 3.6 times higher in females than in males (Badr et al 2012), we chose to conduct the study using female subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, 50 to 77% of respondents in all groups have an elevated BMI. Earlier it was reported by other authors that BMI increases with age, and age is a known risk factor for obesity [7][8][9][10]. Marengoni et al have shown that aging is associated with more than 50% increase in risk for multimorbidity [11].…”
Section: Discussionmentioning
confidence: 95%